2020
DOI: 10.1093/cercor/bhaa298
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Sphingomyelinase is an Affective Valence-Dependent Regulator of Learning and Memory

Abstract: Sphingolipids and enzymes of the sphingolipid rheostat determine synaptic appearance and signaling in the brain, but sphingolipid contribution to normal behavioral plasticity is little understood. Here we asked how the sphingolipid rheostat contributes to learning and memory of various dimensions. We investigated the role of these lipids in the mechanisms of two different types of memory, such as appetitively and aversively motivated memory, which are considered to be mediated by different neural mechanisms. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The activity of sphingolipid enzymes was quantified using fluorescent substrates, BODIPY-FL-C12-Sphingomyelin (D-7711, Invitrogen, Carlsbad, CA, USA/Life Technologies, Grand 15 Island, NY, USA) for S-ASM and NSM (Kalinichenko et al 2021a;Kalinichenko et al 2021b) and NBD-C12-ceramide (Cay10007958-1, Cayman Chemical, via Biomol GmbH, Hamburg, Germany) for neutral ceramidase (Kalinichenko et al 2021c) as described previously (Mühle and Kornhuber 2017). Briefly, the reaction was performed in 96 well polystyrene plates with 58 or 50 pmol fluorescently labelled sphingomyelin or Cer, respectively, in a buffer mix totaling 50 µl in volume.…”
Section: Enzyme Activity Assays For Sphingomyelinase and Ceramidasementioning
confidence: 99%
“…The activity of sphingolipid enzymes was quantified using fluorescent substrates, BODIPY-FL-C12-Sphingomyelin (D-7711, Invitrogen, Carlsbad, CA, USA/Life Technologies, Grand 15 Island, NY, USA) for S-ASM and NSM (Kalinichenko et al 2021a;Kalinichenko et al 2021b) and NBD-C12-ceramide (Cay10007958-1, Cayman Chemical, via Biomol GmbH, Hamburg, Germany) for neutral ceramidase (Kalinichenko et al 2021c) as described previously (Mühle and Kornhuber 2017). Briefly, the reaction was performed in 96 well polystyrene plates with 58 or 50 pmol fluorescently labelled sphingomyelin or Cer, respectively, in a buffer mix totaling 50 µl in volume.…”
Section: Enzyme Activity Assays For Sphingomyelinase and Ceramidasementioning
confidence: 99%
“…NSM is highly expressed in the brain [ 39 , 40 ]. Mice without NSM function in neurons showed a perturbed Golgi secretory pathway, dysproteostasis and impaired learning and memory [ 41 , 42 ]. In the present study, mice with partially reduced NSM function drank less alcohol, possibly because alcohol reduced their affective advantage, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…NSM enhances the excitability of hippocampal CA1 neurons [ 46 , 47 ]. Individual differences in NSM activity in this brain region predispose for efficient learning and adaptations in particularly appetitively motivated long-term memory tasks [ 42 , 48 , 49 ]. An enhanced capacity of the DH may serve better stress resistance and reduce depression-like behaviour, and provide resilience during initiation of alcohol use [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPES (encoded by CG4585 ) and Drosophila SM synthase-related protein (dSMSr) largely govern CPE biosynthesis in flies, in contrast to SM biosynthesis in the mammalian system predominantly mediated by SM synthase 1 and 2 (SMS1 and SMS2) [ 32–34 ]. Common to both mammalian and Drosophila systems, acid and neutral sphingomyelinases (aSMase and nSMase) mediate the conversion of CPE (or SM) into ceramides based on the pH of the microenvironment [ 35 , 36 ]. A previous study showed that Drosophila cpes mutants exhibited photosensitive epilepsy [ 31 ].…”
Section: Introductionmentioning
confidence: 99%